The metabolism and disposition of GSK2140944 in healthy human subjects. (2nd August 2016) - Negash, Kitaw; Andonian, Clara; Felgate, Clive; Chen, Cathy; Goljer, Igor; Squillaci, Bianca; Nguyen, Dung; Pirhalla, Jill; Lev, Mally; Schubert, Ernest; Tiffany, Courtney; Hossain, Mohammad; et al.
Abstract: 1. GSK2140944 is a novel bacterial topoisomerase inhibitor in development for the treatment of bacterial infections. The metabolism and disposition in healthy human subjects was investigated. 2. Six male subjects received [ 14 C] GSK2140944 orally (2000 mg) and as a single 2-hour i.v. infusion (1000 mg). Urinary elimination (59%) was major by the i.v. route, whereas fecal elimination (53%) pre-dominated via the oral route. Accelerator mass spectrometry (AMS) was used for the analysis of plasma and bile samples due to the low level of radioactivity in samples (low specific activity of the doses). Unchanged GSK2140944 was the predominant circulating component (>60% DRM), with the main circulating metabolite M4 formed by oxidation of the triazaacenaphthylene moiety representing 10.8% (considered major) and 8.6% drug-related material by the oral and i.v. route, respectively. Approximately 50% of the oral dose was absorbed and eliminated mainly as unchanged GSK2140944 in urine (∼20% of dose). Elimination via metabolism (∼13% of dose) was relatively minor. The facile oxidation of GSK2140944 to metabolite M4 was believed to be a result of activation by adjacent electron withdrawing groups. 3. This study demonstrates the use of AMS to overcome radioprofiling challenges presented by low specific activity resulted from high doses administration.